2022
DOI: 10.1177/01945998221093527
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Fine‐Needle Aspiration With Molecular Analysis in Management of Indeterminate Thyroid Nodules

Abstract: Objective To analyze clinical outcomes in a series of indeterminate thyroid nodules (ITNs) with repeat fine-needle aspiration (FNA) biopsy and results of genomic classifier. Study Design Historical chart review. Setting Tertiary care center. Methods We reviewed FNA samples from subjects with Bethesda III or IV diagnoses from January 2015 to December 2018 at a single institution and selected those with repeat FNA and ThyroSeq testing of the same nodule. Patient demographics, Bethesda classifications, ThyroSeq r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…[1][2][3] Given the relatively low probability of malignancy associated with these two categories, we and other institutions have preferentially pursued management strategies based on repeat FNA rather than immediate diagnostic surgery. [4][5][6][7][8] In our practice, patients whose nodules are classified as AUS or FN on initial FNA have routinely undergone a repeat FNA procedure to collect duplicate samples for cytology and potential molecular testing with either the Afirma Gene Expression Classifier (GEC) (Veracyte, Inc) 9 or its successor, the Afirma Genomic Sequencing Classifier (GSC) (Veracyte, Inc). 10 The Bethesda classification of the repeat FNA helps determine which samples should be sent out for molecular testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Given the relatively low probability of malignancy associated with these two categories, we and other institutions have preferentially pursued management strategies based on repeat FNA rather than immediate diagnostic surgery. [4][5][6][7][8] In our practice, patients whose nodules are classified as AUS or FN on initial FNA have routinely undergone a repeat FNA procedure to collect duplicate samples for cytology and potential molecular testing with either the Afirma Gene Expression Classifier (GEC) (Veracyte, Inc) 9 or its successor, the Afirma Genomic Sequencing Classifier (GSC) (Veracyte, Inc). 10 The Bethesda classification of the repeat FNA helps determine which samples should be sent out for molecular testing.…”
Section: Introductionmentioning
confidence: 99%
“…For nodules classified in the cytologically indeterminate categories of atypia of undetermined significance (AUS, Bethesda‐III) or follicular neoplasm (FN, Bethesda‐IV), current follow‐up options include repeat FNA biopsy, molecular testing, and/or diagnostic lobectomy 1–3 . Given the relatively low probability of malignancy associated with these two categories, we and other institutions have preferentially pursued management strategies based on repeat FNA rather than immediate diagnostic surgery 4–8 . In our practice, patients whose nodules are classified as AUS or FN on initial FNA have routinely undergone a repeat FNA procedure to collect duplicate samples for cytology and potential molecular testing with either the Afirma Gene Expression Classifier (GEC) (Veracyte, Inc) 9 or its successor, the Afirma Genomic Sequencing Classifier (GSC) (Veracyte, Inc) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the importance of repeat FNA in thyroid nodules with an initial AUS diagnosis. Repeat FNA establishes a definitive diagnosis (TBSRTC category II or VI) in up to 50% of nodules with an initial diagnosis of AUS, reducing unnecessary surgical intervention in benign nodules and providing useful pre‐operative information for malignant nodules 10,11,15,16 . However, a notable portion of nodules remained as AUS after repeat aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the pretest probability of malignancy (thus the performance characteristics of Afirma GSC) is similar whether (1) an endocrinologist/surgeon's assessment of concerning clinical/sonographic features is used to refine the selection of a nodule for potential molecular testing based on the initial AUS diagnosis or (2) repeat diagnosis of AUS is used to refine the selection of a nodule for potential molecular testing.Several studies have demonstrated the importance of repeat FNA in thyroid nodules with an initial AUS diagnosis. Repeat FNA establishes a definitive diagnosis (TBSRTC category II or VI) in up to 50% of nodules with an initial diagnosis of AUS, reducing unnecessary surgical intervention in benign nodules and providing useful pre-operative information for malignant nodules 10,11,15,16. However, a notable portion of nodules remained as AUS after repeat aspiration.…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are non-coding single-stranded RNAs that play a significant role in cancer development, progression, and diagnosis. miRNAs have been studied in various cancers, especially thyroid cancer; a diagnostic tool using miRNAs has been developed and commercially used [ 6 , 7 ]. A previous study investigated the feasibility of using miRNA expression to detect metastatic cells in formalin-fixed paraffin-embedded (FFPE) lymph nodes [ 8 ] and hypothesized that necrosis from tumor progression might provide information about cancer despite its pathology results only showing necrosis.…”
Section: Introductionmentioning
confidence: 99%